2016
DOI: 10.1007/s11145-016-9686-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential lexical predictors of reading comprehension in fourth graders

Abstract: The mental lexicon plays a central role in reading comprehension (Perfetti & Stafura, 2014). It encompasses the number of lexical entries in spoken and written language (vocabulary breadth), the semantic quality of these entries (vocabulary depth), and the connection strength between lexical representations (semantic relatedness); as such, it serves as an output for the decoding process and as an input for comprehension processes. Although different aspects of the lexicon can be distinguished, research on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 42 publications
1
23
0
7
Order By: Relevance
“…For reading comprehension, it has been shown that word reading fluency and listening comprehension are important predictors (Hoover & Gough, 1990). In addition, vocabulary has been found to be a contributor to reading comprehension (Cromley & Azevedo, 2007;Swart et al, 2017). The relation between vocabulary and reading comprehension is especially strong in poor comprehenders.…”
mentioning
confidence: 99%
“…For reading comprehension, it has been shown that word reading fluency and listening comprehension are important predictors (Hoover & Gough, 1990). In addition, vocabulary has been found to be a contributor to reading comprehension (Cromley & Azevedo, 2007;Swart et al, 2017). The relation between vocabulary and reading comprehension is especially strong in poor comprehenders.…”
mentioning
confidence: 99%
“…Previous research has suggested this connection (Hall, Greenberg, Laures-Gore, & Pae, 2014;Swart et al, 2017), but our study is one of the first to examine a direct connection between lexical processes and efficiency. Also, this is one of the first to find a relationship between reading comprehension and lexical processes in adults.…”
Section: Discussionmentioning
confidence: 80%
“…Our findings are consistent with those of other studies. Swart et al (2017) attempted to predict a mean of several measures of a semantic task from several variables related to the lexicon. He also used other measures, such as reasoning and decoding, and was able to explain 65% of the variation in the semantic tasks, but only 30% of the variation was related to lexical measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations